PENYERAPAN LEKSIKON ASING DALAM BIDANG OTOMOTIF KE DALAM BAHASA INDONESIA: TINJAUAN SECARA MORFOLOGIS DAN FONOLOGIS - Nani Darheni (Fakultas Seni Rupa dan Desain ITB, 2009)
The use of foreign terms in the field of automotive absorbed into Indonesian can enrich Indonesian lexicons and positively affects the development of Indonesian. From morphological point of view, foreign terms in the field of automotive can derive from morphological process: (1) affixation, (2) reduplication, (3) abbreviation. While from phonological point of view, the absorption of foreign terms in the field of automotive into Indonesian can be categorized into four: (a) full absorption, (b) absorption through the letter adjustment, (c) absorption through the letter adjustment and translation, (d) absorption through translation. Keywords: absorption, morphology, phonology, foreign terms, automoti